Mobilização dos conceitos estatísticos: um estudo diagnóstico desses conceitos, envolvendo variabilidade, com alunos do ensino médio - Vasques, Ricardo Sergio Braga (2007)
Nowadays it has become habitual to cite Statistics during daily conversations. It´s is possible to perceive how much this sector has gained space and recognition of the people, so, it´s necessary since early to increase the knowledge in this area. It´s very usual professionals of many sectors to come across with statistical problems and can´t solve them, neither because they don´t have the practice, nor because they´ve never seen something about that; it makes us think the problem is behind, in the knowledge acquired at School times. The proposal of this work is analyzing if students of High School of Public Schools are prepared to salve questions with notions of Statistics, as well as the level of knowledge of this students. And it´s exactly what we pretend to verify and to point in this research. The analysis of the questions were made with the software C.H.I.C. (Implicative and Coesitive Hierarchical Classification), that made possible to evidence the Inter-relations found in the answers. We will try to catch the main found difficulties, the imperfections in the learning extracted through the activities proposals as situation-problem, and the capacity of the pupils to decide and to interpret these questions. And then we will trace a parallel to find the diagnosis of these joined problems